Changes in tree diversity and carbon stock over a decade in two Indian tropical dry evergreen forests. Issue 1 (2nd January 2021) - Naveen Babu, K.; Harpal, Biswajit; Parthasarathy, N.
ABSTRACT: Repeated and continuous monitoring of changes in a habitat provides a platform to investigate concurrent variation in the structure, species composition, and function of a forest. We assessed tree diversity and carbon stock changes in two Indian tropical dry evergreen forest (TDEF) sites namely Sendhirakillai (SK) and Palvathunnan (PT) after 10-year time scale. Two 1-ha plots were delimited one in each disturbed and undisturbed site in 2007 and re-measurements were undertaken in 2017. Over the sampling period, species richness showed little variation in both the sites. Out of 38 species identified, 26 species decreased in abundance, nine increased, and three remained unchanged. A total of 860 trees were lost from both the sites in 10-year interval. Site PT witnessed maximum loss (44% – 559 stems). Tree species density, basal area, and carbon stocks decreased tremendously in all girth classes at site PT. Total biomass and carbon stocks were decreased by 42% in site PT and conversely, they increased by 9% in site SK. The substantial difference noticed between the two sites highlights the impact of human disturbance and the need for periodical biodiversity assessment through re-census in Indian TDEFs and also in similar global dry tropical forests.